Early disease progression of Hurler syndrome. Issue 1 (December 2017) - Kiely, Bridget; Kohler, Jennifer; Coletti, Hannah; Poe, Michele; Escolar, Maria
Abstract Background Newborn screening for mucopolysaccharidosis type I (MPS I) shows promise to improve outcomes by facilitating early diagnosis and treatment. However, diagnostic tests for MPS I are of limited value in predicting whether a child will develop severe central nervous system disease associated with Hurler syndrome, or minimal or no central nervous system involvement associated with the attenuated phenotypes (Hurler–Scheie and Scheie syndromes). Given that the optimal treatment differs between Hurler syndrome and the attenuated MPS I phenotypes, the absence of a reliable prognostic biomarker complicates clinical decision making for infants diagnosed through newborn screening. Information about the natural history of Hurler syndrome may aid in the management of affected infants, contribute to treatment decisions, and facilitate evaluation of treatment effectiveness and prognosis. Thus, the aim of this study was to characterize the progression and timing of symptom onset in infants with Hurler syndrome. Results Clinical data from 55 patients evaluated at a single center were retrospectively reviewed. Information about each child's medical history was obtained following a standardized protocol including a thorough parent interview and the review of previous medical records. All patients underwent systematic physical and neurodevelopmental evaluations by a multidisciplinary team. Nearly all patients (98%) showed signs of disease during the first 6 months of life. Common early disease manifestations included failed newborn hearing screen, respiratory symptoms, difficulty latching, and otitis media. Other symptoms such as kyphosis, corneal clouding, cardiac disease, joint restrictions, and enlarged head circumference typically appeared slightly later (median age, 8–10 months). During the first 12 months, gross motor development was the most severely affected area of functioning, and a significant number of patients also experienced language delays. Cognition was typically preserved during this period. Conclusions In this large cohort of patients with Hurler syndrome, the vast majority showed signs and symptoms of disease during the first months of life. More research is needed to determine the extent to which early clinical manifestations of MPS I can predict phenotype and treatment outcomes.